2020
DOI: 10.3390/molecules25163592
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Selenium as a Component of Preservation Solutions for Kidney Transplantation

Abstract: Selenium has strong antioxidant properties and diverse effects on the immune system. The aim of the study was to analyse the protective effect of selenium as a component of a kidney preservation solution on the prevention of ischemia-reperfusion injury of nephrons. The solution was modified by the addition of Se (1 µg/L), prolactin (0.1 µg/L) and Se with prolactin (1 µg/L Se + 0.1 µg/L PRL). The study used a model for storing isolated porcine kidneys in Biolasol® (modified Biolasol®), which minimizes ischemia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The results of the biochemical tests performed in the control and study groups are presented in Figures 1-7. The indirect method, i.e., determination of the activity of enzymes ALT, AST, and LDH, was used to diagnose the degree of damage to kidney cells, which intensifies during ischaemia [48][49][50][51]. The selected markers are sensitive indicators of damage to the structural integrity of the graft.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the biochemical tests performed in the control and study groups are presented in Figures 1-7. The indirect method, i.e., determination of the activity of enzymes ALT, AST, and LDH, was used to diagnose the degree of damage to kidney cells, which intensifies during ischaemia [48][49][50][51]. The selected markers are sensitive indicators of damage to the structural integrity of the graft.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we used Biolasol as a base to evaluate the effectiveness of pharmacological substances in flushing and preserving grafts. We have shown that prolactin (PRL, dose: 1 µg/L) [51,57], lutropin (LH, dose: 0.01 µg/L) [58], and selenium (Se 4+ , dose: 1 µg/L) [48] have a beneficial protective effect on the kidneys. The addition of Zinc to the Biolasol composition at a dose of 1 µg/L showed minor effectiveness in the protection of nephrons [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kidneys were collected according to the previously described procedure [ 52 ]. The grafts were randomly assigned to 4 groups and preserved by static cold storage.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the biochemical markers of renal function were determined. Diagnostic tests were applied, allowing for indirect assessment of renal function [ 10 , 52 , 53 , 54 ]. The graft samples for biochemical analysis in kidney homogenates were collected after 48 h 30 min.…”
Section: Methodsmentioning
confidence: 99%